Insight to the Biochemical Mechanism of the Bone Morphogenetic Protein (BMP6) as an Iron-Regulatory Protein in Iraqi Patients with Iron Deficiency Anemia - Ne’ama, Naba N.; AlNaffi, Karim O.; Auda, Atheer H.; Hameed, Rana M. (Scientific Journal of Medical Research, 2022)
Liver has emerged as the major site of systemic iron regulation, being the location where the iron regulatory hormone hepcidin is produced. Hepcidin is a negative regulator of iron absorption and recycling, achieving this by binding to the only known cellular iron exporter ferroportin and causing its internalization and degradation, thereby reducing iron efflux from target cells and reducing serum iron levels. Bone morphogenetic proteins (BMPs) are members of the transforming growth factor-beta (TGF-?) superfamily of signaling molecules. It has a central role in iron homeostasis. Specifically, BMP6 serves to relate hepatic iron stores to the hepatocellular expression of the iron regulatory hormone hepcidin. Systemic iron regulation maintains a stable concentration of iron transferrin in plasma and extracellular fluid. Therefore, this review was aimed to tracking the biochemical mechanism of the BMP6 as an iron-regulatory protein to provide further insight into their clinical applications, also to suggest areas where further research is needed, either to deal with gaps in the knowledge related to their important roles in a wide array of processes.